Hierarchical Pores‐Confined Ultrasmall Cu Nanoparticles for Efficient Oxidation of 5‐Hydroxymethylfurfural. Issue 13 (30th March 2022) - Lu, Qingwen; Zhao, Xin; Fang, Ruiqi; Li, Yingwei
Abstract: Pyrolysis is one of the most widely utilized protocols for the preparation of nanoconfined metal species for heterogeneous catalysis, but it still suffers from the uncontrollable composition evolution process with undesired metal sintering and porous structure collapse. Herein, a novel and versatile molten salt‐assisted pyrolysis strategy was demonstrated for the preparation of ultrasmall transition‐metal nanoparticles embedded in hollow hierarchical carbon skeletons. The preparation only involved the fabrication of metal‐organic framework templates and subsequent pyrolysis with the addition of KCl−KBr molten salt, which played a crucial role in pore size extending and metal sintering inhibiting. Benefitting from the encapsulation effect, the as‐synthesized Cu@HHC materials exhibited remarkable catalytic performance and recycling stability in the selective oxidation of biomass‐derived 5‐hydroxymethylfurfural into 2, 5‐diformylfuran under mild reaction conditions. Abstract : Encapsulation : Ultrasmall transition‐metal based nanoparticles embedded in hollow hierarchical carbon skeletons are prepared using molten salt as the modulator for inhibiting metal sintering and extending the pore sizes of the metal‐organic framework‐derived carbon support. Benefitting from the encapsulation effect, the as‐synthesized Cu@HHC materials exhibit remarkable catalytic performance and recycling stability in the selective oxidation of biomass‐derived 5‐hydroxymethylfurfural into 2, 5‐diformylfuran under mild reaction conditions.